Synthesis, molecular features and biological activities of modified plant polysaccharides - Mukherjee, Shuvam; Jana, Subrata; Khawas, Sadhana; Kicuntod, Jintawee; Marschall, Manfred; Ray, Bimalendu; Ray, Sayani (Carbohydrate Polymers, 2022)
Plant polysaccharides represent a natural source material characterized by high ubiquity, abundance and biological activities that can be utilised as organic matter in numerous manufacturing processes including pharmaceutical. The goal-oriented modification of polysaccharides by chemical reactions brings about a substantial refinement in their molecular features and biological activity. An improved understanding of the intrinsic molecular features of plant polysaccharides, as well as the structure-activity relationship eventually caused by chemical alterations, may be fundamental for the development of technologies supporting their biomedical oriented exploitation. Herein, we attempt to provide a broader view on these topics and to illustrate methodologies of chemical modification. These are intended to enhance the functionality of plant polysaccharides, such as their modification-induced biological activities, finally making the products available for translational purposes.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Biological activities; Chemical modifications; Molecular features; Plant polysaccharides; Structure-activity relationship